STRATEGI PENGEMBANGAN PRODUK UNGGULAN DAERAH MELALUI KEBIJAKAN PEMERINTAH DAERAH KABUPATEN BONDOWOSO - Nian Riawati (NATAPRAJA, 2018)
This research resulted in the superior product development strategy of Bondowoso Regency that is tape. By analyzing tape problems from upstream to downstream, the results of the analysis resulted in policy recommendations for the development of superior products of Tape Bondowoso. The research approach used is Qualitative with Descriptive Method by explaining the context and setting naturally. The results of this study provide an overview, first, Decrease in Cassava Production caused cassava farmers to switch to other commodities such as coffee or corn. Second, the pattern of cassava farming is still traditional. Third, the lack of skills (life skills) owned by cassava farmers. Fourthly, the instability of cassava prices caused cassava farmers to suffer losses. Fifth, Difficulty Accessing Capital and the market.